Effect of Temperature and Storage on Seed Germination in Populus ciliata Wall. Ex Royle in Garhwal Himalaya - Sah, V. K.; Singh, Virendra (Indian Forester, 1995)
°The study was undertaken to find out the effect of temperature and storage of P. ciliata seeds. The results indicated that the maximum germination was obtained at 20°C. The seeds stored at +2°C retained better viability (60.5%) than the seeds stored at -10°C (30.0%) after one year of storage period.